Uncovering the essence of moving experiences in Japanese culture: Development and validation of a kando reaction scale. - Haruka Shoda; Shoko Yasuda; Ai Uemiya; Atsushi Yuhaku; Tadao Isaka (PLoS ONE)
Kando is a Japanese term referring to a spectrum of reactions associated with feeling moved experiences. This study developed an instrument to measure an individual's degree of kando and its associated reactions and explored how Japanese people experience kando in their lives. As part of a large-scale survey, we analyzed data from 4,690 Japanese participants aged 20-69. In the survey, participants recalled and described their most significant kando events and rated their experiences on a provisional kando reaction scale consisting of 43 items. The results indicated that the most significant kando events could be grouped into eight clusters: family issues, interpersonal relationships, arts, sports, travel/nature, negative issues, achievements, and religion/disaster. Using exploratory and confirmatory factor analyses, we constructed a 33-item kando reaction scale with a correlated 11-factor structure. The degree of kando and its relevant reactions differed as functions of event clusters and population characteristics such as sex and age. For example, kando on family issues generated multiple, somewhat contrasting, responses such as happiness and hardship. Intense arousal when experiencing kando tended to increase depending on the individual's age. Our kando reaction scale can be a useful instrument for describing and exploring psychological mechanisms relevant to kando.